2016
DOI: 10.1515/ncrs-2015-0303
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of N′-(4-(dimethylamino)benzylidene)-5-phenyl-1H-pyrazole-3-carbohydrazide, C19H19N5O

Abstract: C 19 H 19 N5O, triclinic, P¯ (no. 2), a = 11.8865(6) Å, b = 12.6289(7) Å, c = 13.5579 (7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A review of the literature has revealed that substituted pyridazinones have received a lot of attention in recent years because of their significant potential as antimicrobial (Sö nmez et al, 2006), antidepressant (Boukharsa et al, 2016), antiinflammatory (Barberot et al, 2018), antihypertensive (Siddiqui et al, 2011), analgesic (Gö kçe et al, 2009), anti-HIV (Livermore et al, 1993), anticonvulsant (Partap et al, 2018;Sharma et al, 2014), cardiotonic (Wang et al, 2008), antihistaminic (Tao et al, 2012), glucan synthase inhibitors (Zhou et al, 2011), phosphodiesterase (PDE) inhibitors (Ochiai et al, 2012) and herbicidal agents (Asif, 2013). In continuation of our work in this field (El Kali et al, 2019;Chkirate et al, 2019a,b;Karrouchi et al, 2015Karrouchi et al, , 2016a, we report the synthesis and the crystal and molecular structures of the title compound, as well as an analysis of its Hirshfeld surface.…”
Section: Chemical Contextmentioning
confidence: 78%
“…A review of the literature has revealed that substituted pyridazinones have received a lot of attention in recent years because of their significant potential as antimicrobial (Sö nmez et al, 2006), antidepressant (Boukharsa et al, 2016), antiinflammatory (Barberot et al, 2018), antihypertensive (Siddiqui et al, 2011), analgesic (Gö kçe et al, 2009), anti-HIV (Livermore et al, 1993), anticonvulsant (Partap et al, 2018;Sharma et al, 2014), cardiotonic (Wang et al, 2008), antihistaminic (Tao et al, 2012), glucan synthase inhibitors (Zhou et al, 2011), phosphodiesterase (PDE) inhibitors (Ochiai et al, 2012) and herbicidal agents (Asif, 2013). In continuation of our work in this field (El Kali et al, 2019;Chkirate et al, 2019a,b;Karrouchi et al, 2015Karrouchi et al, , 2016a, we report the synthesis and the crystal and molecular structures of the title compound, as well as an analysis of its Hirshfeld surface.…”
Section: Chemical Contextmentioning
confidence: 78%
“…Pyridazinones are used as scaffolds for potential drug candidates (Dubey & Bhosle, 2015;Thakur et al, 2010) because of their significant potential as antimicrobial (Sö nmez et al, 2006), antidepressant (Boukharsa et al, 2016), anti-inflammatory (Barberot et al, 2018), antihypertensive (Siddiqui et al, 2011), analgesic (Gö kçe et al, 2009), anti-HIV (Livermore et al, 1993), anticonvulsant (Partap et al, 2018;Sharma et al, 2014), cardiotonic (Wang et al, 2008), antihistaminic (Tao et al, 2012), glucan synthase inhibitors (Zhou et al, 2011), phosphodiesterase (PDE) inhibitors (Ochiai et al, 2012) and herbicidal (Asif, 2013) agents. ISSN 2056-9890 In this context and in a continuation of our work in this field (Chkirate et al, 2019a,b;Karrouchi et al, 2015Karrouchi et al, , 2016a, we report herein the synthesis and the molecular and crystal structures of the title pyridazinone derivative, together with its Hirshfeld surface analysis.…”
Section: Chemical Contextmentioning
confidence: 86%